Perfil dos visitantes na Floresta Nacional do Tapajós, Pará, Brasil - FIGUEIRA, Tainá Santos (Universidade Federal do Oeste do Pará, 2024)
The Tapajós National Forest is one of the most visited Conservation Units in the Northern Region of Brazil and has as one of its objectives the promotion of communitybased tourism. Considering the variety in the profile of visitors that frequent it, this study sought to evaluate the visitor profile in the communities São Domingos, Maguari, Jamaraquá and in the Demonstrative Site of Terra Rica, as well as to identify their expectations, experiences, motivations and the tourism segments that operate there. For data collection a questionnaire was used, applied during the months of December 2020 to July 2021. Most visitors are women, the age range of visitors is between 21 and 30 years old, their monthly income is higher than three minimum wages, they have a high level of education, and the most prominent issuing states were Pará and São Paulo. The interviewees interpreted their experience as "ecotourism" or "nature tourism" and evaluated their experience positively. The study showed that visitors to the Tapajós National Forest are basically divided between hikers and tourists. It is necessary to adopt strategies to improve the number of visitors and their experience at the site.